2006
DOI: 10.1111/j.1471-4159.2006.04237.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and evolution of the mammalian brain gene Ttyh1

Abstract: Homologues of the Drosophila melanogaster tweety (tty) gene are present in mammals and Caenorhabditis elegans. The encoded proteins have five predicted membrane-spanning regions and recent findings suggest that some family members may be chloride channels. Phylogenetic analysis of the tty family including novel members from slime mould Entamoeba and plants has revealed the occurrence of independent gene duplication events in different lineages. expressed sequence tag data indicate that expression of the mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 21 publications
9
67
0
Order By: Relevance
“…Expression of hTTYH3 in CHO cells generated a unique Clcurrent activated by an increase in the intracellular Ca 2+ concentration. Overexpression of Tthy1 shows that it is a membrane protein [18] . Using constructs for overexpression of Httyh-1, -2 and-3 in CHO and HEK cell lines [23,24] , Suzuki et al suggested that hTTYH1 activation is calcium-independent but that of hTTYH2 and hTTHY3 are strongly calcium-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of hTTYH3 in CHO cells generated a unique Clcurrent activated by an increase in the intracellular Ca 2+ concentration. Overexpression of Tthy1 shows that it is a membrane protein [18] . Using constructs for overexpression of Httyh-1, -2 and-3 in CHO and HEK cell lines [23,24] , Suzuki et al suggested that hTTYH1 activation is calcium-independent but that of hTTYH2 and hTTHY3 are strongly calcium-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…3), and recent reports indicate a similar role in cortical neuroepithelial cells and radial precursor cells (Arai et al, 2005;Barry and McDermott, 2005). A role for Ttyh1 in cell adhesion and possibly as a transmembrane receptor in astrocytoma has also been suggested (Matthews et al, 2007). Similarly, Hmgb2, Id3, and cell cycle-related genes may play important roles in the proliferation of mDA neuron precursors but in a manner distinct from Fabp7.…”
Section: In E15 Ebf1mentioning
confidence: 97%
“…The expression of Ttyh1 mRNA is restricted to neural tissue and the testis [8]. In the brain, Ttyh1 mRNA has been detected in neurons [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, Ttyh1 mRNA has been detected in neurons [9, 10]. The expression of Ttyh1 protein is also neuronal and has been detected in neurons in vivo and in vitro [6, 8, 11]. The overexpression of Ttyh1 protein in cell lines and neurons in vitro leads to excessive filopodia formation [8, 11].…”
Section: Introductionmentioning
confidence: 99%